2023
DOI: 10.21203/rs.3.rs-2692165/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The association between hypoalbuminemia and microcirculation, endothelium and glycocalyx disorders in children with sepsis.

Abstract: Background Endothelial inflammation and activation in sepsis can alter albumin synthesis and increase its loss. In these patients, hypoalbuminemia tends to be associated with worse outcomes. The consequences of hypoalbuminemia for the microcirculation of children with sepsis are unknown. We evaluated the association between hypoalbuminemia and microcirculation disorders, endothelial activation and glycocalyx degradation in this group of patients. Methods This was an observational, analytical, prospective coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have also demonstrated a consistent correlation between low levels of albumin and unfavorable prognosis among sepsis patients. Furthermore, it has been identi ed as a highly reliable predictor of mortality in this population [21][22][23] . Although serum albumin levels can be used as a general marker of the severity of a sepsis patient's condition, albumin is an acute-phase protein that uctuates as the patient's condition uctuates [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also demonstrated a consistent correlation between low levels of albumin and unfavorable prognosis among sepsis patients. Furthermore, it has been identi ed as a highly reliable predictor of mortality in this population [21][22][23] . Although serum albumin levels can be used as a general marker of the severity of a sepsis patient's condition, albumin is an acute-phase protein that uctuates as the patient's condition uctuates [24] .…”
Section: Discussionmentioning
confidence: 99%